Population, Resources and Development Riding the Age Waves - Volume 1 - Tuljapurkar, Shripad; Pool, Ian; Prachuabmoh, Vipan (International Studies in Population,, 2005)
In the 21st century, the populations of the world's nations will display large and long-lived changes in age structure. Many of these began with fertility change and are amplified by declining mortality and by migration within and between nations. Demography will matter in this century not by force of numbers, but by the pressures of waves of age structural change. Many developing countries are in relatively early stages of fertility decline and will experience age waves for two or more generations. These waves create shifting flows of people into the key age groups, greatly complicating the task of managing development, from building human capabilities and creating jobs to growing industry, infrastructure and institutions. In this book, distinguished scientists examine key demographic, social, economic, and policy aspects of age structural change in developing economies. This book provides a joint examination of dimensions of age structural change that have often been considered in isolation from each other (for example, education, job creation, land use, health); it uses case studies to examine policy consequences and options and develops qualitative and formal methods to analyze the dynamics and consequences of age structural change.